Binding Abilities and Extractive Applications of Nano-baskets of Calixarenes - Mokhtari, Bahram; Pourabdollah, Kobra (Asian Journal of Chemistry, 2011)
Because of the recent rapid growth in the publications about applications of nano-baskets of calixarene in extraction of ionic and molecular species, this review paper has focused on different extractive applications of calixarene derivatives. The objectives and the results of about 140 references that were published in recent 6 years with emphasis on the binding ability and extractive applications were reviewed. A tutorial algorithm was designed to explain the recent advances in binding ability of calixarene and their applications in extractions of analytical chemistry. The applications of calixarene derivatives to bind and extract the seven following fields were reviewed, including alkali and alkaline earth metals, p-block cations, transition metals, actinides and lanthanides, molecular species, organic cations and anions.